Prostate-specific Antigen (PSA) Density and Free to Total PSA Ratio in Diagnosing Prostate Cancer with Prostate-Specific Antigen Levels of 4.0 ng/ml or Less - Liu, Xin; Tang, Jie; Fei, Xiang; Li, Qiu-Yang (Iranian journal of public health, 2015)
We aimed to value the usefulness of free to total prostate-specific antigen and Prostate-specific antigen (PSA) density for prostate cancer in the patients with PSA levels of 4.0 ng/ml or less. A total of 343 subjects with PSA levels of 4.0 ng/ml or less were biopsied. All patients were divided into four groups according to the PSA levels: 0 to 1.0 ng/ml, 1.1 to 2.0 ng/ml, 2.1 to 3.0 ng/ml, and 3.1 to 4.0 ng/ml. The reliability of cancer detection in relation to the f/t PSA ratio and PSAD were estimated. Overall, 65 people were diagnosed with prostate cancer. The detection rate was 16.28%、17.17%, 21.82%, 25.00% in subjects with PSA levels of 0 to 1.0 ng/ml, 1.1 to 2.0 ng/ml, 2.1 to 3.0 ng/ml, and 3.1 to 4.0 ng/ml, respectively. The f/t PSA ratio was significantly lower in patients with prostate cancer and PSA levels of 2.1 to 4.0 ng/ml (P<0.05). The PSAD had no statistical significance between the two groups. Routine prostate biopsy should be undertaken if the f/t PSA ratio less than 15% with /without abnormal DRE/TRUS findings.